O ANNE, RUSE PROLETARCE. TRANSFORMATIONS OF THE INTENTION OF OLBRACHT'S NOVEL IN THE CONTEXT OF THE PROPAGANDA GOALS OF THE COMMUNIST PARTY OF CZECHOSLOVAKIA - Piorecka, Katerina (Bohemica Olomucensia, 2022)
The study focuses on a textual analysis of the first edition of Ivan Olbracht's novel O Anne, ruse proletarce, which appeared in the magazine Reflektor, published by the Communist Party of Czechoslovakia in 1925 and 1926. It was at this time that the Communist Party of Czechoslovakia, in line with the demands of the Third International, transformed its propaganda and began to use its magazines to agitate politically indifferent readers. To do this, it deliberately uses 'means of art and entertainment'. In the context of the Party's propaganda and agitation department's regulations, Olbracht, in the middle of the novel and simultaneously with the new edition of Reflektor magazine, retreats from the title character's love affair, a genre from which the magazine Komunistka, unlike Reflektor, aimed at female readers, had also retreated by that time. The figure of the maid-mother-proletarian Anna recedes into the background and is replaced by a series of male characters who illustrate the various attitudes and opinions of the Czechoslovak left in 1920. Along with these, the author also experiments with other popular genres: reportage, the adventure novel, and the detective story. This external circumstance led critics of the book to conclude that Anna proletarka, even after the author's revision, did not become a collective novel that would create a synthetic image of its time. However, the political context, in which Ivan Olbracht was expelled from the Communist Party of Czechoslovakia along with six other writers, led to the fact that even in its first book edition, Anna proletarka did not become a successful agitational novel. That happened only after another rewrite in 1946.
Keywords: Ivan Olbracht; Anna proletarka; Communist Party of Czechoslovakia; propaganda; popular literature